Turning the tables: A university league-table based on quality not quantity [version 2; peer review: 2 approved] - Adrian G. Barnett; David Moher (F1000Research, 2019)
Background: Universities closely watch international league tables because these tables influence governments, donors and students. Achieving a high ranking in a table, or an annual rise in ranking, allows universities to promote their achievements using an externally validated measure. However, league tables predominantly reward measures of research output, such as publications and citations, and may therefore be promoting poor research practices by encouraging the “publish or perish” mentality. Methods: We examined whether a league table could be created based on good research practice. We rewarded researchers who cited a reporting guideline, which help researchers report their research completely, accurately and transparently, and were created to reduce the waste of poorly described research. We used the EQUATOR guidelines, which means our tables are mostly relevant to health and medical research. We used Scopus to identify the citations. Results: Our cross-sectional tables for the years 2016 and 2017 included 14,408 papers with 47,876 author affiliations. We ranked universities and included a bootstrap measure of uncertainty. We clustered universities in five similar groups in an effort to avoid over-interpreting small differences in ranks. Conclusions: We believe there is merit in considering more socially responsible criteria for ranking universities, and this could encourage better research practice internationally if such tables become as valued as the current quantity-focused tables.